Spermatocytic Tumor Arising in a Cryptorchid Testis: A Case Report and Narrative Review - Laurențiu Augustus Barbu; Stelian-Stefaniță Mogoantă; Liliana Cercelaru; Marius Cristian Marinaș; Nicolae-Dragoș Mărgăritescu; Mihai Popescu; Valentina Căluianu; Gabriel Florin Răzvan Mogoș; Liviu Vasile; Tiberiu Stefăniță Țenea Cojan (Journal of Clinical Medicine, 2026)
Background: Spermatocytic tumor (ST) is a rare non-GCNIS-derived testicular germ cell neoplasm that predominantly affects older men and generally follows an indolent course. Its occurrence in a cryptorchid testis is exceptionally uncommon. Methods: A narrative literature review was conducted using the PubMed database, including studies published up to August 2026. The search used combinations of the terms “spermatocytic tumor”, “spermatocytic seminoma”, “cryptorchidism”, “undescended testis”, “immunohistochemistry”, “molecular features”, “magnetic resonance imaging”, and “treatment”. Results: A 56-year-old man presented with a painless left inguinal mass corresponding to a cryptorchid testis. Serum tumor markers were normal. MRI demonstrated a well-circumscribed heterogeneous lesion with pseudocystic areas and enhancement of the solid component. Radical inguinal orchiectomy was performed. Histopathological examination revealed the characteristic triphasic cellular population without GCNIS, lymphovascular invasion, or sarcomatous transformation. Immunohistochemistry showed SALL4 and CD117 positivity and absence of OCT3/4 and D2-40 expression, supporting the diagnosis of ST and its distinction from classical seminoma. No recurrence or metastatic disease was detected during 12 months of follow-up. Conclusions: ST arising in a cryptorchid testis represents an exceptionally uncommon presentation. Integration of clinical, radiological, morphological, and immunohistochemical findings is essential for accurate diagnosis and distinction from classical seminoma, thereby avoiding unnecessary additional treatment.